2020
DOI: 10.1101/2020.12.21.423852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial approach of binary colloidal crystals (BCCs) and CRISPR activation to improve induced pluripotent stem cell differentiation into neurons

Abstract: Conventional methods of neuronal differentiation for human induced pluripotent stem cells (iPSCs) are tedious and complicated, involving multi-stage protocols with complex cocktails of growth factors and small molecules. Artificial extracellular matrix with defined surface topography and chemistry represents a promising venue to improve the neuronal differentiation in vitro. In the present study, we test the impact of a type of colloidal self-assembled patterns called binary colloidal crystals (BCCs) in neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The advantage of silica nanoparticle delivery methods is that they are biocompatible and can be modified according to three different delivery forms: plasmid DNA, mRNA, and CRNP. Several studies have demonstrated the potential of silica nanoparticles to deliver CRISPR-Cas9 in vivo to treat melanoma and deliver to retinal pigment epithelium124 and induce pluripotent stem cells (iPSCs) [116][117][118].…”
Section: Other Non-virus Vectorsmentioning
confidence: 99%
“…The advantage of silica nanoparticle delivery methods is that they are biocompatible and can be modified according to three different delivery forms: plasmid DNA, mRNA, and CRNP. Several studies have demonstrated the potential of silica nanoparticles to deliver CRISPR-Cas9 in vivo to treat melanoma and deliver to retinal pigment epithelium124 and induce pluripotent stem cells (iPSCs) [116][117][118].…”
Section: Other Non-virus Vectorsmentioning
confidence: 99%